Crystallization of amorphous‐Si using nanosecond laser interference method. Issue 1 (16th November 2018) - Kang, Min Jin; Kim, Minyeong; Hwang, Eui Sun; Noh, Jiwhan; Shin, Sung Tae; Cheong, Byoung‐Ho
Abstract: Laser crystallization of a 50‐nm thick amorphous‐Si (a‐Si) thin film on glass substrate was examined by a Nd:YAG (λ = 1064 nm) nanosecond laser and a two‐beam laser interference method. In spite of the low absorption rate of the laser wavelength in the a‐Si, crystallized Si ripple patterns were observed following a single laser pulse irradiation. The atomic force microscope (AFM) measurement revealed that surface ripple arrays are protruded as high as 120 nm at the positions corresponding to the maximum laser intensity and the ripples are composed of narrow double peaks with a separation of 1 μm. Raman image mapping was used to plot the spatial distribution of the crystallized Si phase. It was found that a 1064‐nm‐wavelength nanosecond laser could crystallize an a‐Si thin film into polycrystalline‐Si (poly‐Si) by nonlinear absorption under high laser energy irradiation. Abstract : Laser crystallization of an amorphous‐Si (a‐Si) thin film was examined by an Nd:YAG (1064 nm) nanosecond laser and a two‐beam laser interference method. In spite of the low absorption rate of the laser wavelength in the a‐Si, crystallized Si ripple patterns were observed following a single laser pulse irradiation. The atomic force microscope measurement revealed that surface ripple arrays are protruded as high as 120 nm at the positions corresponding to the maximum laser intensity and the ripples are composed of narrow double peaks with a separation of 1 μm.